Phenol composition, DPPH radical scavenging and antimicrobial activity of cornelian cherry (Cornus mas) fruit and leaf extracts - Milenković-Anđelković Ana S. (Hemijska Industrija, 2015)
Fruit is rich in different phenolic compounds which are recognized as potential natural medicaments and have been used in folk medicine for centuries. In order to evaluate phenol composition, cornelian cherry (Cornus mas) fruit and leaf extracts were subjected to the spectrophotometric and HPLC analysis. The radical scavenging activity was estimated using DPPH test and antimicrobial activity by disc diffusion and microwell dilution tests. All extracts showed high phenol content from 89.89 ± 0.45 to 117.34 ± 1.40 mg f gallic acid equivalents GAE/g extract dry matter DM but different composition of phenol compounds. Flavonols, anthocyanins, flavan-3-ols and phenolic acids were the main phenol classes found in the investigated fruit and leaf extracts. All extracts showed significant radical scavenging activity and a correlation with total phenol content (R2 = 0.9832). Significant antimicrobial activity was found against Gram-positive, followed by Gram-negative strains, and yeast in all tested extracts. Cornelian cherry fruit and leaf extracts, rich in phenolic content, with significant antiradical and antimicrobial activity, can be used as additives in food and medicaments. [Projekat Ministarstva nauke Republike Srbije, br. 34012, br. 31020 and br 176006 and EU, FP7 - Regpot - 2007- 3-01, the project «Chromlab-Antioxidant», No. 204756]